Les voyages de savants en Europe et le développment des Idées géographiques dans le Portugal du XIXe siècle - Dévy-Vareta, Nicole (Finisterra, 1998)
SCIENTIFIC TRAVELS AND THE DEVELOPMENT OF GEOGRAPHICAL IDEAS IN PORTUGAL DURING THE 19TH CENTURY - The main goal of this paper is to establish the relationship between scientists movements, the circulation of ideas and the appearance of some basic works for modern Portuguese geography, around 1870. The break between a purely descriptive geography and modern geography is traditionally situated in the 1870's. Perhaps it was prepared by the contacts established inside Europe between scientists. It seems that natural sciences, agronomy and forest science had leading roles in this process. On this subject, we will try to explore the official missions and the stay of portuguese students in Northern Europe. This way, we will be able to trace the contribution of the ideas of Bernardino de Barros Gomes, who contributed towards the development of geographic thought a long time before geography became a University institution.